The Association of Obesity with Isolated Systolic Hypertension: Evidence from a Nationwide Survey in Mongolia - Dechmaa J; Bolormaa I; Otgontuya D; Davaalkham D; Narantuya D (Disease and Health: Research Developments Vol. 2, 2024)
Purpose: To determine the association of obesity with Isolated systolic hypertension among people aged 15-64 years. Materials and Methods: The study design is a population-based cross-sectional study. An association of obesity with Isolated systolic hypertension (ISH) using data from the “Mongolian STEPS Survey on the prevalence of non-communicable disease and injury risk factors-2009” was examined. A total of 5456 people participated in this study. ISH was defined as systolic blood pressure\(\)140 mmHg and diastolic blood pressure<90 mmHg. Body weight, height, waist circumference, body fat content, and blood pressure were measured in all survey participants. One in three survey participants was tested for blood glucose, cholesterol, triglycerides, low-density lipoprotein and high-density lipoprotein in serum. Results: Mean body weight, mean body mass index and waist circumference in people with ISH were statistically and significantly higher compared to the people with normal blood pressure. The prevalence of obesity in the group with ISH was 21.3 percent. It was statistically and significantly higher than in the normotensive group (11.6 percent) (p=0.0001). The prevalence of central obesity was 55.0 percent in the group with ISH and 45.0 percent in the normotensive group. In terms of gender, central obesity was 76.3 percent in females with ISH and 42.0 percent in males with ISH (p=0.0001). The findings demonstrate that the prevalence of central obesity is significantly higher among females with ISH than males. Body fat content was high and very high in 66.6 percent of the people with ISH and in 50.5 percent of the people with normal blood pressure (p=0.0001). Body fat content is higher in the group with ISH compared to the normotensive group without gender difference. (p=0.0001) . The association between obesity and ISH by univariate logistic regression analysis was studied. As the study result, the risk of ISH is 1.5 times more in people with central obesity, 2.3 times more in the obese by BMI, and 2.1 times more in people with increased body fat (p=0.003, p=0.0001). On confirmation of multiple logistic regression analysis, age, gender, central obesity, excessive salt intake and increasing blood glucose were independent risk factors for ISH. Central obesity, excessive salt intake and increasing blood glucose are related to the lifestyle of people and those are modifiable risk factors for ISH. Conclusions: It was revealed in our study that among 15-64-year-olds, an increase in body mass index, fat content and waist circumference are risk factors for Isolated systolic hypertension. The prevalence of central obesity is significantly higher among females with ISH than males. The risk for Isolated systolic hypertension is 2 times higher in people with central obesity.